Patient Perspective on Acute Intermittent Porphyria with Frequent Attacks: A Disease with Intermittent and Chronic Manifestations - Simon, Amy (Patient, 2018)
OBJECTIVE: Acute intermittent porphyria is a rare metabolic disorder that affects heme synthesis. Patients with acute intermittent porphyria may experience acute debilitating neurovisceral attacks that require frequent hospitalizations and negatively impact quality of life. Although clinical aspects of acute intermittent porphyria attacks have been documented, the experience of patients is not well known, particularly for those more severely affected patients who experience frequent attacks. The aim of the present study was to qualitatively characterize the experience of patients with acute intermittent porphyria who have frequent attacks, as well as the impact of the disease on daily living. METHODS: Patients with acute intermittent porphyria who experience frequent attacks were recruited and took part in 2-h qualitative one-on-one interviews with a semi-structured guide. Interviews were anonymized, transcribed, and coded. The inductive coding approach targeted textual data related to acute intermittent porphyria attack symptoms, chronic symptoms, and the impact of the disease. Saturation analysis was conducted to assess whether the research elicited an adequate account of patients’ experiences. RESULTS: In total, 19 patients with acute intermittent porphyria were interviewed (mean age 40 years; 79% female). Eighteen patients (95%) experienced both attack and chronic symptoms. Patients described attacks as the onset of unmanageable symptoms that generally lasted 3–5 days requiring hospitalization and/or treatment. Pain, nausea, and vomiting were considered key attack symptoms; pain, nausea, fatigue, and aspects of neuropathy (e.g., tingling and numbness) were considered key chronic symptoms. CONCLUSIONS: In this study population of acute intermittent porphyria with frequent attacks, most patients had symptoms during and between attacks. In these patients, acute intermittent porphyria appears to have acute exacerbations as well as chronic day-to-day manifestations, and is not just intermittent as its name implies. As a result, patients reported limitations in their ability to function across multiple domains of their lives on a regular basis and not just during acute attacks. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40271-018-0319-3) contains supplementary material, which is available to authorized users.